BBS/BBF ENCAPSULATED MICROORGANISMS TECHNOLOGY FOR SOLID INOCULATION, THE NEXT STEP TO NOT USE WATER IN BIOLEACHING PROCESSES WITH HIGH PERFORMANCE - Piña, Patricia; Martinez, Patricio (My University, 2018)
Industrial hydrometallurgical processes using copper oxides and mixed oxide/sulfide exhibit high concentrations of several ions in their raffinates that hinder the treatment of copper ores with microorganisms because they are strongly affected by ionic impurities. On the other hand, water costs and hydric balance of processes in some mining sites, especially in desert areas, make it impossible to use fresh water for the dilution of toxic solutions and compatibility of the microbial activity in the bioleaching process. A strategy to address this in bioleaching applications has not been solved with an economical sustainable way.
Keywords: BioSigma Bioleaching Seeds Technology; Copper Sulfide Ore; Encapsulated Biomining Consortium